Choroidal Thickening in Patients with Sleep Apnea Syndrome. (February 2014) - Ekinci, Metin; Hüseyinoğlu, Nergiz; Hüseyin Çağatay, H.; Keleş, Sadullah; Ceylan, Erdinç; Gökçe, Gökçen
Abstract Sleep apnoea syndrome (SAS) is characterised by repetitive episodes of cessation of breathing during sleep, resulting in hypoxaemia and hypercapnia. Ophthalmological consequences such as glaucoma, non-arteritic anterior ischaemic neuropathy and papilloedema are relevant to hypoxaemia. The choroid is a vascular structure that performs several regulatory functions for the retina. Defects in this structure contribute to degenerative, inflammatory, and neovascular changes in the retina. The authors examined the choroidal thickness (CT) in sleep apnoea patients using optical coherence tomograpy (OCT). The sleep apnoea patients were divided into subgroups according to their apnoea-hypopnoea index (AHI) scores, and statistical analysis was performed using the AHI and minimal arterial oxygen saturation (min. Spo2) values. There was a medium-high negative correlation between CT and AHI (Spearman rho: r = −0.744, p = 0.000), and a positive correlation between CT and min. Spo2 values (Pearson correlation: r = 0.308, p = 0.000).